ANALISIS FAKTOR YANG MEMPENGARUHI HIRSCHSPRUNG DI RUMAH SAKIT PROF. DR. MARGONO SOEKARJO PURWOKERTO - Suryandari, Artathi Eka (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Hirschsprung is a complex genetic disease with a low, sex-dependent penetrance and is the most common cause of neonatal obstruction of the colon. The incidence 1 : 4400 to 1 : 7000 live birth. The male/female ratio in patient with classic hirschsprungâ€™s disease is generally reported as 4 : 1. The purpose of this study is to analyze the factors that affect the incidence of hirschsprung disease in Prof. Hospital. Dr. Margono Soekarjo Purwokerto. The research method used is with case control design. The population in this study were patients with hirschsprung disease and patients who were not diagnosed with hirschsprung disease. The sample of this study amounted to 42 cases and 42 controls. Univariate data were analyzed descriptively while for bivariate data was analyzed by chi square. The results showed that maternal age did not affect the occurrence of hirschsprung (Ï-value: 0.649) and sex influenced the occurrence of hirschsprung (Ï-value: 0,042). Keywords: hirschsprung, age, gender